Cyclic fatigue resistance of HyFlex EDM, Reciproc Blue, WaveOne Gold, and Twisted File Adaptive rotary files under different temperatures and ambient conditions - Mustafa Gündoğar; Taha Özyürek; Koray Yılmaz; Gülşah Uslu (Tabriz University of Medical Sciences, 2019)
Background. This study examined the effects of changes in temperature and environmental conditions on the cyclic fatigue resistance of Reciproc Blue, HyFlex EDM, WaveOne Gold, and Twisted File Adaptive. Methods. Forty-five Reciproc Blue (25/.08), 45 HyFlex EDM (25/.08), 45 WaveOne Gold (25/.07), and 45 Twisted File Adaptive (25/.08) files were tested for cyclic fatigue at room temperature (20°C) in air and water and at body temperature (35°C) in water. All the instruments were rotated in artificial canals made of stainless steel with an inner diameter of 1.5 mm, 60° angle of curvature and a radius of curvature of 5 mm until fracture occurred; the time to fracture was recorded in seconds, using a digital chronometer. Mann-Whitney U test was used for the statistical analysis of data, with SPSS 21.0. Results. Cyclic fatigue resistance was significantly higher in all the groups in water at an ambient temperature of 20°C compared with air and water at temperatures of 20°C and 35°C, respectively (P<0.05). The intragroup analysis revealed that HyFlex EDM had the highest cyclic fatigue resistance, followed by Reciproc Blue, WaveOne Gold, and Twisted File Adaptive in both air and water at 20°C (P<0.05). HyFlex EDM exhibited the highest cyclic fatigue resistance in water at 35°C, whereas there was no significant difference between the other groups (P>0.05). Conclusion. Within the limitations of the present study, an increase in the ambient temperature significantly decreased the cyclic fatigue resistance of the tested NiTi files.